PENDUGAAN VOLUME TEGAKAN BERDASARKAN JUMLAH DAN KERAPATAN TAJUK PADA FOTO UDARA - Ishak Sumantri; Haryono Haryono; Machfudh Machfudh (Jurnal Penelitian Hasil Hutan, 1986)
SummaryThe relationship description of stumpage  volume  over the crown densities and number of crown which is measured on serial photos  are the object of this study.  The study  was conducted  research take at a tropical rain forest  which have been harvested  by using the Indonesia  Selective Cutting  (TPI) system  in East Kalimantan.   The model  analysis reveals that:1.    The distribution  of crown densities (%) and number  of crown data are normally  distributed.2.   The relationship  of stumpage  volume  over the crown densitys percentage  and number  of crown can be expressed as: V   =    -169.  7132 + 3.8514N  + 2.8532  + 0.0004C2    + 0.014CNWhere:    V  :  Stumpage  volume,  (m3)N   :  Numbers  of crown,  unitlessC   :  Crown, densitys,  %.Coefficient  of determination  (R)   =   0. 7828. This model  is significant  at 95%   level after  tested by F-test.3.   The model  and its analysis only valid in East Kalimantan.